2015
DOI: 10.15376/biores.10.2.2570-2584
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Some Woody Tree Methanolic Extracts and Paraloid B-72 against Phytopathogenic Mold Fungi Alternaria tenuissima and Fusarium culmorum

Abstract: Natural compounds from certain timber trees are highly valued and recommended to protect wood and wood products against mold fungi. This study highlighted the use of some natural extracts and Paraloid B-72 against the growth of two mold fungi, namely Alternaria tenuissima and Fusarium culmorum. From the in vitro experiment, the methanol extracts of Callistemon viminalis bark were effective against the growth of F. culmorum, as were Magnolia grandiflora leaves against A. tenuissima. Environmental scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…On the other hand, a combination of Paraloid B-72 (10%) with Pentachlorophenol 2% showed antifungal activity against A. flavus [35]. Wood treated with Paraloid B-72 (2% or 3%) showed huge mycelial growth of Trichoderma harzianum [33], Alternaria tenuissima, and Fusarium culmorum [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a combination of Paraloid B-72 (10%) with Pentachlorophenol 2% showed antifungal activity against A. flavus [35]. Wood treated with Paraloid B-72 (2% or 3%) showed huge mycelial growth of Trichoderma harzianum [33], Alternaria tenuissima, and Fusarium culmorum [34].…”
Section: Discussionmentioning
confidence: 99%
“…Paraloid was used for the consolidation of paper-based manuscripts, and its mixture with NPs was shown to increase or improve the mechanical and optical properties of papers [28,29], and wooden artifacts [30]. Paraloid B-72 at 2%, 3%, or 10% did not exhibit antifungal activity [30][31][32][33][34], but antifungal activity of Paraloid B-72 (10%) was observed when mixed with other substances [35].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of wood treated with an acetone extract of W. somnifera fruits was measured according to National Committee for Clinical Laboratory Standards (NCCLS) [51] with minor modifications, wherein the treated wood samples were placed over the inoculated medium with each bacterium at 30 • C for three days and compared with the control treatment. For antifungal activity, the fungal isolates were grown at 28 • C and the wood-treated samples were assayed according to previous studies [41][42][43]50], with measurement of the mycelial growth inhibition percentage performed. The inhibition zone (IZ) was measured from the outer margin of the IZ to the inner margin of the surrounding pathogens, including the treated wood blocks for bacteria, and the IZ was measured from the edge of the treated wood blocks to the outer margin of the surrounding pathogens for the fungi.…”
Section: Antimicrobial Activity Of Wood Treated With Acetone Extractmentioning
confidence: 99%
“…On the other hand, and during storage conditions with moist and poor environments, wood, wood containers, and wood-boxes may deteriorate or become stained with the growth of molds [36], which colonize these wood types and use simple sugars and starches for growth [37,38]. Previous works have shown that extracts or essential oils have potential antimicrobial activities against several fungi and bacteria in treated wood of Pinus sylvestris, P. rigida and Fagus sylvatica, Leucaena leucocephala, Melia azedarach, and Acacia saligna [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The measurements of antifungal activity of treated wood were carried out following previous works (Mansour and Salem ; Mansour et al . ; Salem et al . ,).…”
Section: Methodsmentioning
confidence: 99%